Study of Web Content Mining and Its Tools (International Journal of Engineering and Computer Science, 2014)
This paper presents the details of searching or extracting information from the web. It also discusses main tasks involved in web mining. It mainly focuses on the types of Web Content mining such as Unstructured, Structured and Semi-structured types. Finally, some tools that are used for mining is also focused in this paper.